Reduced insulin clearance differently relates to increased liver lipid content and worse glycemic control in recent-onset type 2 and type 1 Diabetes - Zaharia, Oana-Patricia; Antoniou, Sofia; Bobrov, Pavel; Karusheva, Yanislava; Bódis, Kálmán; Kupriyanova, Yuliya; Schrauwen-Hinderling, Vera; Gastaldelli, Amalia; Szendrödi, Julia; Wagner, Robert; Burkart, Volker; Roden, Michael (Diabetes care, 2023)
Diabetes may feature impaired insulin kinetics, which could be aggravated by altered hepatic metabolism and glycemic control. Thus, we examined insulin clearance and its possible determinants in individuals with recent-onset diabetes.Participants of the German Diabetes Study (GDS) with type 1 diabetes (T1D) (n = 306), type 2 diabetes (T2D) (n = 489), or normal glucose tolerance (control [CON]) (n = 167) underwent hyperinsulinemic-euglycemic clamps for assessment of whole-body insulin sensitivity (M value) and insulin clearance (ICCLAMP). Insulin clearance rates were further calculated during intravenous glucose tolerance tests (ICIVGTT) and mixed-meal tests (ICMMT). Hepatocellular lipid content (HCL) was quantified with 1H-MRS.Both T1D and T2D groups had lower ICCLAMP (0.12 ± 0.07 and 0.21 ± 0.06 vs. 0.28 ± 0.14 arbitrary units [a.u.], respectively, all P < 0.05) and ICMMT (0.71 ± 0.35 and 0.99 ± 0.33 vs. 1.20 ± 0.36 a.u., all P < 0.05) than CON. In T1D, ICCLAMP, ICIVGTT, and ICMMT correlated negatively with HbA1c (all P < 0.05). M value correlated positively with ICIVGTT in CON and T2D (r = 0.199 and r = 0.178, P < 0.05) and with ICMMT in CON (r = 0.176, P < 0.05). HCL negatively associated with ICIVGTT and ICMMT in T2D (r = −0.005 and r = −0.037) and CON (r = −0.127 and r = −0.058, all P < 0.05). In line, T2D or CON subjects with steatosis featured lower ICMMT than those without steatosis (both P < 0.05).Insulin clearance is reduced in both T1D and T2D within the first year after diagnosis but correlates negatively with liver lipid content rather in T2D. Moreover, insulin clearance differently associates with glycemic control and insulin sensitivity in each diabetes type, which may suggest specific mechanisms affecting insulin kinetics.